The Structural Model for Predicting Psychological Well-Being in Adolescents with Nomophobia Based on Socioeconomic Status with the Mediating Role of Emotion Regulation - Bahrampouri, Leila; Gholamitooranposhti, Marzieh; Ghamari, Mohammad (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to develop and test a structural model predicting psychological well-being in adolescents with nomophobia based on socioeconomic status, with the mediating role of emotion regulation.Methods and Materials: The study employed a descriptive–correlational design with an applied objective. The statistical population consisted of all female secondary school students with nomophobia in Tehran during the 2023–2024 academic year. Using multistage cluster sampling, 304 participants were selected from four districts of Tehran. Data were collected using the Nomophobia Questionnaire (Azadmanesh et al., 2016), Ryff’s Psychological Well-Being Scale – Short Form (Ryff, 1989), the Socioeconomic Status Questionnaire (Ghodratnama, 2013), and the Emotion Regulation Questionnaire (Gross & John, 2003). Data analysis was conducted using Pearson correlation tests, confirmatory factor analysis, and structural equation modeling with SPSS-V27 and AMOS-V3.3.Findings: Results indicated that socioeconomic status was positively and significantly related to psychological well-being in adolescents with nomophobia. Reappraisal, as a strategy of emotion regulation, showed a positive and significant association with psychological well-being (β = 0.312, p < 0.001), while suppression exhibited a negative and significant relationship with psychological well-being (β = -0.270, p < 0.001). The mediating analysis demonstrated that reappraisal significantly mediated the relationship between socioeconomic status and psychological well-being (β = 0.096, p = 0.008), whereas suppression did not yield a significant mediating effect (p = 0.181). The overall structural model explained 69% of the variance in psychological well-being among adolescents with nomophobia.Conclusion: The findings highlight the pivotal role of socioeconomic status and emotion regulation strategies in shaping psychological well-being in adolescents with nomophobia. While higher socioeconomic status directly supports well-being, adaptive strategies such as reappraisal enhance these effects, whereas suppression undermines them.